DNA Barcoding Analysis of Mullet (Planiliza sp.) using the Cytochrome C Oxidase Sub Unit I (COI) Gene in Merauke Coastal Waters - Saleky, Dandi; Situmorang, Ferdinand C; Welliken, Marius A.; sembiring, Jefri (Jurnal Ilmiah PLATAX, 2025)
Conservation genetics is an one effort to explore the potential of fish resources and maintain their sustainability. Fishes are important of biodiversity and are generally found in various ecosystems, including coastal, swamp and river ecosystems. The aim of this research is to analyze and identify important fish species using DNA barcoding techniques and phylogenetic analysis using GEN Cytochrome C Oxidase Sub Unit I (COI). Results of DNA amplification obtained a DNA sequence length of 665 bp with the identification result being mullet (Planiliza alata) with 100 % of similarity level. The resulting phylogenetic tree shows species grouping based on genetic distance and level of DNA sequence similarity. Based on this data, molecular approaches can be used to support aquatic resource conservation activities through conservation genetics. Keywords: Planiliza alata, DNA Barcoding, phylogenetic, COI Gene Abstrak Salah satu upaya untuk menggali potensi sumberdaya ikan dan mempertahankan kelestariannya adalah dengan genetika konservasi. Spesies ikan merupakan bagian penting dari keanekaragaman hayati dan umumnya ditemukan di berbagai ekosistem baik ekosistem pesisir, rawa, dan sungai. Tujuan penelitian ini adalah menganalis dan mengidentifikasi spesies ikan ekonomis penting menggunakan Teknik DNA barcode dan analisis filogenetik menggunakan GEN Cytochrome C Oxidase Sub Unit I (COI). Hasil amplifikasi DNA diperoleh panjang sekuen DNA 665 bp dengan hasil identifikasi adalah ikan belanak (Planiliza alata) dengan tingkat kemiripan 100 %. Pohon filogenetik yang dihasilkan menunjukkan pengelompokan spesies berdasarkan jarak genetik dan tingkat kemiripan sekuen DNA. Berdasarkan data ini, pendekatan molekuler dapat digunakan untuk mendukung kegiatan konservasi sumberdaya perairan melalui genetika konservasi. Kata Kunci: Planiliza alata, DNA Barcoding, Filogenetik, Gen COI.